Single-electron spectra in RPWELL-based detectors. (4th May 2021) - Bhattacharya, P.; Tesi, A.; Shaked-Renous, D.; Moleri, L.; Breskin, A.; Bressler, S.
Abstract: Single-electron spectra are the key ingredient in the efficient detection of single UV-photons. In this work, we investigated the shape of single-photoelectron spectra in single- and double-stage Resistive Plate WELL (RPWELL) detector configurations, operated in Ne/CH4 and Ar/CH4 . Discharge-free operation was reached over a broad dynamic range, with charge gains of [range-phrase = -]e4e6. Compared to the usual exponential ones, the observed Polya-like charge spectra pave the way towards higher single-electron detection efficiencies. The latter was evaluated here, using experimental data combined with numerical simulations. The effects of the gas mixtures, electric field configuration, and detector geometry on the Polya spectra and their related "θ" parameter are presented.